1992
DOI: 10.2214/ajr.158.3.1738995
|View full text |Cite
|
Sign up to set email alerts
|

Myometrial invasion by endometrial carcinoma: assessment by MR imaging.

Abstract: In patients with early-stage endometrial cancer, preoperative knowledge of myometrial tumor extension has important prognostic and therapeutic implications. The purpose of this prospective study was to determine the sensitivity and specificity of MR imaging for assessing the depth of myometrial invasion in patients with endometrial cancer that clinically was thought to be confined to the uterine cOrpus. Sixty-five consecutive patients were included in the study. All patients had MR imaging before radical surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 10 publications
3
57
0
2
Order By: Relevance
“…Pelvic MRI is an examination accepted in the characterisation of pelvic tumours due to its multiplanar capacity and its excellent resolution of soft tissue contrast (Cunha et al 2001;Sironi et al 1992a;Sironi et al 1992b). High accuracy in the assessment of the depth of myometrial infiltration (superficial/deep) as well as the extent of cervical invasion and identification of enlarged pelvic and para-aortic lymph nodes has been described in the literature (Cunha et al 2001;Manfredi et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Pelvic MRI is an examination accepted in the characterisation of pelvic tumours due to its multiplanar capacity and its excellent resolution of soft tissue contrast (Cunha et al 2001;Sironi et al 1992a;Sironi et al 1992b). High accuracy in the assessment of the depth of myometrial infiltration (superficial/deep) as well as the extent of cervical invasion and identification of enlarged pelvic and para-aortic lymph nodes has been described in the literature (Cunha et al 2001;Manfredi et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The reported accuracy of non-contrast-enhanced MR imaging for assessing the depth of myometrial invasion ranges between 74% and 97% (1,4,5,6,7,16,19). Hricak et al (1), in a prospective study of 88 patients, obtained an overall accuracy with MRI of 85%.…”
Section: Discussionmentioning
confidence: 99%
“…Interruption of the junctional zone with overlying intact myometrium implies superficial invasion, which is classified as stage Ib. Invasion of more than 50% of the myometrium with an intact outer rim is graded as a deep invasion, or stage Ic [27,30,31] (Table 1). Overestimation of tumor invasion can occur in cases with bulky masses that stretch and thin, rather than invade, the myometrium.…”
Section: Endometrial Cancermentioning
confidence: 99%
“…Most commonly, the tumor appears hypointense to the myometrium on early phase images. Superficial myometrial invasion is diagnosed when disruption of the inner myometrial enhancement is identified [32][33][34], whereas the diagnosis of deep myometrial invasion requires demonstration of focal thinning of the myometrium or evidence of direct tumor extension to the outer myometrium [30][31][32][33][34].…”
Section: Endometrial Cancermentioning
confidence: 99%